Neuron secrete exosomes containing miR-9-5p to promote polarization of M1 microglia in depression - Xian, Xian; Cai, Li-Li; Li, Yang; Wang, Ran-Chao; Xu, Yu-Hao; Chen, Ya-Jie; Xie, Yu-Hang; Zhu, Xiao-Lan; Li, Yue-Feng (Journal of nanobiotechnology, 2022)
Background Neuroinflammation is an important component mechanism in the development of depression. Exosomal transfer of MDD-associated microRNAs (miRNAs) from neurons to microglia might exacerbate neuronal cell inflammatory injury. Results By sequence identification, we found significantly higher miR-9-5p expression levels in serum exosomes from MDD patients than healthy control (HC) subjects. Then, in cultured cell model, we observed that BV2 microglial cells internalized PC12 neuron cell-derived exosomes while successfully transferring miR-9-5p. MiR-9-5p promoted M1 polarization in microglia and led to over releasing of proinflammatory cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), which exacerbated neurological damage. Furthermore, we identified suppressor of cytokine signaling 2 (SOCS2) as a direct target of miR-9-5p. Overexpression of miR-9-5p suppressed SOCS2 expression and reactivated SOCS2-repressed Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathways. Consistently, we confirmed that adeno-associated virus (AAV)-mediated overexpression of miR-9-5p polarized microglia toward the M1 phenotype and exacerbated depressive symptoms in chronic unpredictable mild stress (CUMS) mouse mode. Conclusion MiR-9-5p was transferred from neurons to microglia in an exosomal way, leading to M1 polarization of microglia and further neuronal injury. The expression and secretion of miR-9-5p might be novel therapeutic targets for MDD. Graphical Abstract